2022
DOI: 10.14309/ajg.0000000000001641
|View full text |Cite
|
Sign up to set email alerts
|

Qualitative Validation of a Novel VR Program for Irritable Bowel Syndrome: A VR1 Study

Abstract: INTRODUCTION:Although gut-directed psychotherapies are effective for irritable bowel syndrome (IBS), they are rarely prescribed, given a paucity of trained clinicians. Virtual reality (VR) offers a solution by allowing patients to self-practice these techniques in a standardized manner.METHODS:A multidisciplinary team developed IBS/VR, a program that transports users into immersive VR worlds that teach patients about the brain-gut axis, cognitive behavioral therapy, and gut-directed meditation. We tested IBS/V… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…308 While VR seemed to be effective for FD, 309 it has yet to be tested as a treatment for IBS. 310 Further studies investigating not only the therapeutic benefits of VR on DGBI as well as the impact of this form of therapy on the microbiome are needed.…”
Section: Current Treatmentsmentioning
confidence: 99%
“…308 While VR seemed to be effective for FD, 309 it has yet to be tested as a treatment for IBS. 310 Further studies investigating not only the therapeutic benefits of VR on DGBI as well as the impact of this form of therapy on the microbiome are needed.…”
Section: Current Treatmentsmentioning
confidence: 99%
“…Although no study has assessed virtual reality for the treatment of IBS to date, a recent RCT demonstrated that virtual reality significantly improved symptoms, including abdominal pain, and quality of life in patients with functional dyspepsia, another common DGBI [36]. Additionally, Spiegel et al [37] recently presented a new virtual reality program designed specifically for the treatment of IBS, validated through patient feedback. To establish virtual reality as a valid treatment option for DGBIs, like IBS, certainly RCTs will be needed; multiple are currently in the planning stages.…”
Section: Brain-gut-directed Therapiesmentioning
confidence: 99%
“…Additionally, Spiegel et al . [37] recently presented a new virtual reality program designed specifically for the treatment of IBS, validated through patient feedback. To establish virtual reality as a valid treatment option for DGBIs, like IBS, certainly RCTs will be needed; multiple are currently in the planning stages.…”
Section: Brain-gut-directed Therapiesmentioning
confidence: 99%